(untitled) (Fiep Bulletin - online, 2023)
Knowledge of general nutrition and healthy eating are fundamental components of university educational training and a multidisciplinary competence in the area of physical education that the future professional must have to achieve optimal performance. The general objective of the work was to determine the level of knowledge of nutrition and food in university students of sports sciences, from the Autonomous University of Asunción, between September and November 2021. It was developed as a non-experimental cross-sectional investigation, with a quantitative approach of descriptive level, on a population of 128 students and a non-probabilistic sample of intentional selection of 103 students through the application of the test "Knowledge about nutrition and general food in tertiary level students of areas related to sports". It was found that only 37% (n=38) have met an approved level of knowledge (22% sufficient and 15% optimal), against 63% (n=64) with deficient levels. On which it was concluded that there is a deficient level of knowledge of nutrition and food in university students, observed significantly on 66% (n = 55) of students between 18 and 24 years old; in 67% (n=18) of women and 61% (n=46) of men, especially over 76% (n=38) of first-year students.